SELF-REPORT MECHANISM BY COMPANIES IN RELATION TO FRAUDULENT ACT OF BRIBERY: A CHANGE IN COMPANY’S LEADERSHIP CULTURE - Carissa Tridina Arsyad Temenggung; Edward Candy; Febri Ariadi; Joviana Henza (Asia Pacific Fraud Journal, 2018)
The purpose of this study is to emphasize that the goal of Criminal Justice System in terms of fraud and other corrupt practices by company (such as bribery), one of the way is to avoid far-reaching consequences, including debarment of the company from the local government. Notwithstanding its immensity, corruption can cause damage to the reputation of the business and jeopardize its profitability. To prevent this from happening, this study will examine the possibility for companies to conduct a self-report mechanism in relation to fraudulent act of bribery, as a way to change company’s leadership culture. By conducting self-report mechanism (as have been implemented in U.S. through the FCPA and U.K. through the UK Bribery act), companies are expected to whistleblow its own wrongful acts to relevant authority, so that their employees are no longer committing fraud, knowing that the company will report them. While on the other hand, the company will gain benefit (such as monetary recoveries, leniency) in conditions that will be explained further in this paper.